2014
DOI: 10.9745/ghsp-d-14-00009
|View full text |Cite
|
Sign up to set email alerts
|

Using behavior change communication to lead a comprehensive family planning program: the Nigerian Urban Reproductive Health Initiative

Abstract: Greater exposure to a comprehensive family planning program in urban Nigeria that emphasized demand generation and communication theory was associated with improved ideation among women (their beliefs, ideas, and feelings about family planning), and more positive ideation was associated with greater contraceptive use, especially among the poor. Improving providers' knowledge, attitudes, and skills was also key. By the end of the observation period, outreach through mobile service delivery contributed nearly on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(99 citation statements)
references
References 11 publications
2
97
0
Order By: Relevance
“…Some potential mediums to consider are one-on-one counseling with patients in family planning clinics, community-based group education programs, or mass media campaigns. While communication campaigns have addressed side effects broadly, to our knowledge past communication programs have rarely if ever directly addressed the belief that contraceptive use causes infertility (Halperin et al 2013;Burke and Ambasa-Shisanya 2014;Krenn et al 2014). The message itself could acknowledge that using contraceptives and becoming a mother are not mutually exclusive, perhaps by role modeling mothers who have previously used family planning methods.…”
Section: Discussionmentioning
confidence: 99%
“…Some potential mediums to consider are one-on-one counseling with patients in family planning clinics, community-based group education programs, or mass media campaigns. While communication campaigns have addressed side effects broadly, to our knowledge past communication programs have rarely if ever directly addressed the belief that contraceptive use causes infertility (Halperin et al 2013;Burke and Ambasa-Shisanya 2014;Krenn et al 2014). The message itself could acknowledge that using contraceptives and becoming a mother are not mutually exclusive, perhaps by role modeling mothers who have previously used family planning methods.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult for wives to initiate the family-planning talk, as many fear the prospect, especially if they suspect that their husband is opposed to contraceptive use 14 . Formative research for Nigerian Urban Reproductive Health Initiative (NURHI) in four states, among them Kaduna State in the north, found that women felt men should start the conversation, and men felt their wives should start the conversation, and so the contraceptive conversation never happened 31 . Poor spousal communication is, in many ways, driven by the many reasons couples want to keep having children, as described above 32 .…”
Section: Who Influences Women's Health Decisions?mentioning
confidence: 99%
“…Considering values, a healthy sexual behaviour involves their identifying or standing by practices that is "right" on the basis of both personal and sociocultural values, which may include compromise, self-control or tolerance. This also includes issues on use contraception to avoid unplanned pregnancy or sexually transmitted disease 21 .Values may also encompass spirituality 20 . For instance, religious people abstain from sexual intercourse during their time of 'prayer and fasting' .…”
Section: The Healthy Sexual Behaviourmentioning
confidence: 99%
“…A cursory search of PubMed, alone, for FPMS, yields thousands of published articles including hundreds arising from any single Low-Mid Income Country (LMIC). Several factors, methods and programs are already known including but not limited to ideas such as behavioural change motivation 21,59 , getting closer to the people 60 , and family education 61 . Other issues of barriers, generational change and provider behaviour have also been identified 62,63 .…”
Section: Implication For Further Studiesmentioning
confidence: 99%
See 1 more Smart Citation